Introduction: secular criticism and the politics of studying Islam - Peter P. Mandaville (Tidsskrift for Islamforskning, 2008)
In recent years many within the European and North American academies whose research engages topics and themes that encompass the study of Islam and Muslim societies have found not only that their subject matter has become the object of frequent and often intense public debate, but also that their scholarship—indeed their very vocation—seems likewise under considerable scrutiny. The public dimension here is important. We are not concerned with a disagreement over the finer points of social theory between otherwise amiable colleagues that plays out through the pages of an obscure academic journal. Rather, we are talking about a state of affairs that has threatened careers and livelihoods, funding streams, and the fundamental basis of academic freedom.